Admission Accounting Information System and Cash Expenditure in Financial Control - Anggerwati, A. Indah (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
Every organization requires a well-planned and properly supervised accounting information system to effectively manage their incoming and outgoing finances. The implementation of an accounting information system is crucial for achieving the management's objectives. This study aims to assess the effectiveness of the accounting information system in managing cash receipts and expenditures, specifically in the context of financial planning and control at the Benteng City Grand Mosque. The research utilizes qualitative data obtained from primary and secondary sources. The descriptive analysis method is employed in this study. The findings indicate that the accounting information system for cash receipts and expenditures, concerning financial planning and control, is deemed sufficient as it aligns with the fundamental components of an accounting information system, including human resources, equipment, forms/documents, records, procedures and reports, and adheres to internal control procedures. Consequently, the accounting information system for cash receipts and expenditures continues to operate effectively to support financial planning and control.